Functional properties of multicomponent galvanic alloys of iron with molybdenum and tungsten - Karakurkchi, A.V.; Ved', M.V.; Sakhnenko, N.D.; Yermolenko, I.Yu.; Zyubanova, S.I.; Kolupayeva, Z.I. (Functional Materials, 2015)
Galvanic alloy coatings Fe-Mo (W) and Fe-Mo-W were deposited from citrate bath based on Fe (III) using both direct and pulsed current on substrates steel 3 and grey cast iron GC 18. It was shown that the alloying components content, their distribution on the surface, morphology and topography of the coatings are depended on the electrolysis mode. It was established that the functional properties of the binary and ternary alloys of iron (corrosion resistance, microhardness, antifriction et al.) exceed parameters of the substrate and are predetermined by the composition, structure, material and surface roughness.